Approach for successful knowledge management system deployment for organizations - Gharamah, Abdulrahman; Noordin, Mohamad Fauzan; Imtiaz Ali, Najma; Brohi, Imtiaz Ali (Science Publishing Corporation Inc, 2018)
Globalization and rivalries are the fundamental two difficulties confronting firms who are attempting to support their prosperity or even to remain in the market. Subsequently; interests in technology, process and people wind up plainly important for the association to guarantee to have fancied offer in the Marketplace. Vast firms set up cutting edge and complex sites and hello tech innovation to make, keep up and share knowledge inside by gathering and applying picked up information to make financial esteem. Knowledge is an imperative concentration in association's methodology, where information is viewed as essential for organizations. Organizations can turn out to be more productive by exchanging and sharing what specialists know, and after that, they can create learning strategies. The fundamental target of this paper is to distinguish existing knowledge management hone with a specific end goal to enhance it. A reasonable guide will be hypothetically proposed to be actualized and embedded in the corporate operations and business system. The pilot study was performed to validate the research questionnaire. The results were within the prescribed range so the researcher is ready to collect the actual data.